The Becket List : a Blackberry Farm story - Griffin, Adele (Algonquin Young Readers, 2019)
When New York City native Becket Branch moves to the country with her family to help run her grandmother's farm and store, she finds that new friends, hostile chickens, sour lemonade and mischief are only the beginnings of her new life.